2017
DOI: 10.1016/j.jneb.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

SNAP-Based Incentive Programs at Farmers' Markets: Adaptation Considerations for Temporary Assistance for Needy Families (TANF) Recipients

Abstract: Objective To describe the design, implementation, and consumer response to a coupon-style intervention aimed to increase Supplemental Nutrition Assistance Program (SNAP) use at a farmers’ market (FM) among Temporary Assistance for Needy Families (TANF) participants. Design Quasi-experimental trial to evaluate redemption response to two coupon interventions; baseline surveys characterized coupon redeemers and non-redeemers. Setting Urban Participants TANF recipients assigned to either a plain (n=124) or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Differences in value may also be important, given that program retention is a challenge across the literature, and programs that provide less value may be less effective in encouraging ongoing participation. Notably, Wetherill et al [41] posited that low incentive redemption rates may be tied to perceived differences in the value of different kinds of incentives, as incentives that function as discounts and expand buying power may be less valuable to participants than incentives that provide free products.…”
Section: Financial Value Of Incentive To Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences in value may also be important, given that program retention is a challenge across the literature, and programs that provide less value may be less effective in encouraging ongoing participation. Notably, Wetherill et al [41] posited that low incentive redemption rates may be tied to perceived differences in the value of different kinds of incentives, as incentives that function as discounts and expand buying power may be less valuable to participants than incentives that provide free products.…”
Section: Financial Value Of Incentive To Participantsmentioning
confidence: 99%
“…In addition, the Healthy Incentives Program also assessed the program impact at various points throughout the implementation phase [7]. A few studies also used control or quasi-control groups to assess program impact [7,34,37,41,47]. The merits of quasi-control groups are somewhat limited if the comparison groups do not share important characteristics with the incentive program participants.…”
Section: Outcome Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Premature spoilage of F&V and knowledge of cooking have also emerged as a barrier to F&V consumption among low-income populations in prior research (9,(25)(26)(27) . A study by Haynes-Maslow and colleagues found that perishability of F&V and cooking/nutrition knowledge emerged as key barriers to F&V purchasing (25) .…”
Section: Discussionmentioning
confidence: 99%